Наукові дослідження в стандартизації ливарного виробництва України - Стригун, В.О.; Волошин, Н.М.; Гнилоскуренко, С.В.; Чаплигіна, Л.С. (Physico-technological Institute of Metals and Alloys, 2023)
The article deals with the important task for the Ukrainian economy, directly related to the reorientation of production to high quality indicators of products – the development of new national standards that are harmonized with International and European standards. For the research, the foundry industry was chosen as the basis of the country’s engineering complex. In particular, the standards for the most important modern structural materials – cast iron, steel and secondary metals – were selected as objects. As a result of the study of the provisions of GOST 977-88 and a number of national and European standards for steel grades and methods for monitoring the chemical composition and mechanical properties of steel castings, the national standard of Ukraine DSTU 8781: 2018 “Steel castings. General specifications” was developed and introduced. The provisions of GOST 1412-82 and a number of national and European standards for cast irons are studied, as a result of which the national standard of Ukraine DSTU 8833: 2019 “Gray iron castings with plate graphite. General specifications” was developed. The term of its issue is 1.01.2020. The provisions of GOST 7769-82 and a number of national and European standards for alloyed cast irons are studied, as a result of which the national standard of Ukraine DSTU 8851: 2019 (ISO 2892: 2007, NEQ, ISO/TR 15931: 2004, NEQ) “Castings from alloyed cast iron with special properties. General specifications” was developed. The term of its issue is 1.07.2020. As a result of the study of the provisions of DSTU 4121-2002, a number of national and European standards, the European specification of steel scrap EU-27, Recommendations for steel scrap FS-2017 of the US Scrap Processing Institute, the first edition of the new national standard “Secondary ferrous metals. General specifications” was developed.